Reclamation of Dye Affected Soil at Tirupur Region by Using Vermitechnology, South India - R. Hariprakash, and V. Balakrishnan*, V. Prabhu, M. Ishwarya, S.R. Kayalvizhi, (Journal of Ecobiotechnology, 2010)
Soil from the dye affected area is taken for various analysis. Similarly soil from the fertile land is also taken for analysis in the same region. Most of the soils polluted by heavy metals can be reclaimed using a number of expensive tactics that either remove the contaminants or stabilize them within the soil .To analyze the parameters such as soil pH, temperature, soil fungal, bacterial and actinomycetes population of both the samples. Find out what are the metals present in the soil samples. Apply vermicompost to the dye affected soil for reclamation. Again we should analyze soil pH, temperature, fungal, bacterial and actinomycetes population of both the soil samples .The results are discussed with the literature. ---------------------------------------------------------------------------------- V. Prabhu, M. Ishwarya, S.R. Kayalvizhi, R. Hariprakash, and V. Balakrishnan* Department of Biotechnology, K.S.Rangasamy College of Technology, Tiruchengode-637 215, Tamilnadu, India *Corresponding Author, Email: palanivbalu@gmail.com Please Cite This Article As: V. Prabhu, M. Ishwarya, S.R. Kayalvizhi, R. Hariprakash, and V. Balakrishnan. 2010. Reclamation of Dye Affected Soil at Tirupur Region by Using Vermitechnology, South India. J. Ecobiotechnol. 2(4):16-21.